Sealing performances of polymer heat-shrinkable tubing for deep rocks under high-temperature and ultrahigh-pressure condition - Heng Gao; Heping Xie; Zetian Zhang; Ru Zhang; Mingzhong Gao; Yihang Li; Ling Chen; Hongxin Xie (Journal of Rock Mechanics and Geotechnical Engineering, 2025)
The deep underground engineering will face high-temperature and ultrahigh-pressure (HTUP) condition. Indoor triaxial testing is an important means to investigate this challenge in rock mechanics and rock engineering. Heat-shrinkable tubing, as a seal on the rock surface, is crucial for reconstructing deep rock in situ conditions (ensuring the accuracy and effectiveness of confining pressure and pore pressure). However, there are few reports on testing such material under HTUP condition. Thus, the mechanical and sealing performances of existing heat-shrinkable tubing under HTUP condition is still immature. The motivation of this study is to advance deep rock mechanics and engineering by developing a polymer heat-shrinkable tubing (pressure larger than 140 MPa and temperature greater than 150 °C). Experiments using the deep rock in situ thermal insulation coring test system were conducted and compared with conventional heat-shrinkable tubing. The sealing performance of the polymer heat-shrinkable tubing was investigated. The results indicated that deep rock ultrahigh-pressure condition and natural damage to the rock surface are the main causes of conventional heat-shrinkable tubing failure. In contrast, the damage rate of the proposed polymer heat-shrinkable tubing is extremely low, indicating that incorporating base material with high-performances can significantly enhance the pressure resistance of polymer heat-shrinkable tubing. Additionally, through the analysis of experimental results and the three-dimensional (3D) morphology of rock surfaces, the failure behavior of heat-shrinkable tubing under HTUP condition was revealed at the meso-structural level, and the proposed failure criteria, taking into account 3D morphology of rock surfaces and applicable to HTUP condition, have been advanced. The findings offer possibilities for triaxial rock mechanics testing in HTUP condition, providing theoretical and technical support for experiments and engineering applications in deep rock mechanics.